If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4y + 1z = 36.39 Solving 6x + 4y + 1z = 36.39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 6x + 4y + -4y + 1z = 36.39 + -4y Combine like terms: 4y + -4y = 0 6x + 0 + 1z = 36.39 + -4y 6x + 1z = 36.39 + -4y Add '-1z' to each side of the equation. 6x + 1z + -1z = 36.39 + -4y + -1z Combine like terms: 1z + -1z = 0 6x + 0 = 36.39 + -4y + -1z 6x = 36.39 + -4y + -1z Divide each side by '6'. x = 6.065 + -0.6666666667y + -0.1666666667z Simplifying x = 6.065 + -0.6666666667y + -0.1666666667z
| -7+7x-x=-1 | | 13-12d^2-35d= | | 10x+-6=7x+9 | | x=4.2375+-0.5y | | x^2+9x+20.25=-2+20.25 | | 9y+-11=-2 | | 4x+2y=16.95 | | 10+-21=7x | | 1507+20x=1767 | | 6c^3+8c^2-30c= | | 7x-27x=0 | | 1507+20=1767 | | 14=-7x+5x+8 | | 22=6(5-4f) | | 4r+6=16 | | F(z)=z^2-2+2 | | 4x+-15=x | | -12x+48=12x+4 | | 4(2x+3)=2(5x-2)+b | | 12x+48=12x+4 | | 12=2x+4/3-2x/3 | | 2(8-4c)=32 | | a+5=3a | | a=5-3a | | x=4x+6 | | 2(6z+1)-8=78 | | 7m-3-2=(5m-2)+6 | | -6a-18=-2a+2 | | 5n+9=49 | | 0.5x=1.25 | | 1.1x=-12.1 | | 5x+8x-9x=8+4 |